Penatalaksanaan Fisioterapi Pada Kasus Low Back Pain Akibat Spondilosis Lumbal 4-5 Di RSUD Dr. Moewardi Surakarta - Radisca, Yellin; , Umi Budi Rahayu S. FT, M. Kes (2015)
Background: Low Back Pain (LBP) or back pain is a common complaint. Almost 70-80% of the population in developed countries have experienced LBP. Causes of back pain vary, but an outline of which is spondilogenik. Spondilogenik back pain is a type derived from the vertebral column and structures related thereto, as well as a cause of back pain is the most important. LBP lumbar spondylosis is a condition found progressive degeneration of intervertebral disc which leads to changes in the border area vertebrae and ligaments, narrowing of the intervertebral foramen. The existence of intervertebral disc degeneration causing clinical symptoms such as pain, weakness of abdominal and back muscles. Methods: This paper uses the case study method to management therapy 6 times. Results: After treatment for 6 times the obtained results of the assessment of pain in lower back pain silent T1: 3 to T6: 2, pain motion T1: 5 to T6: 4, tenderness T1 to T6: 2, increased abdominal muscle strength T1: 3 became T6: 4, muscle strength back up to T6 T1: 4, increased lumbar flexion range of motion T1: 2 cm into T6: 3 cm, increase range of motion of lumbar extension T1: 1 cm to T6: 1 cm, increase ability scores activity functional T1: 24 to T6: 19. Conclusion: From the research that has been done, as evidenced by the use of TENS modalities and therapeutic exercise with William Flexion Exercise therapy for 6 times obtained an increase in impairment, functional limitation and disability.